ALK overexpression without rearrangement widely exists in EWSR1 / FUS -rearranged soft tissue tumours - Lihong Li; Lihua Gong (Journal of Clinical Pathology, 2026)
Aims Anaplastic lymphoma kinase (ALK) is implicated in ALK fusion-positive non-small cell lung cancer and inflammatory myofibroblastic tumours. Based on prior studies and our observations, ALK overexpression appears to be associated with FET ( FUS / EWSR1 / TAF15 ) family rearrangements ( EWSR1 and FUS ). Methods In this study, we analysed 119 FET-rearranged tumours spanning 20 tumour types. Using ALK D5F3 immunohistochemistry (IHC), ALK overexpression was defined as positive only for scores of 2+ or 3+. Cases with ALK overexpression by IHC were further confirmed to lack ALK gene rearrangements. Results Among the cases, 28.6% (34/119) demonstrated ALK overexpression (≥2+). 9 disease types displayed ALK overexpression (≥2+), including soft tissue sarcomas and salivary gland carcinomas. Notably, Ewing sarcoma had the highest ALK overexpression rate (51%, 22/43). Both analysed clear cell sarcoma-like tumour of the gastrointestinal tract (GNET) cases (2/2) were strongly positive (3+), while extraskeletal myxoid chondrosarcoma exhibited a high overexpression rate (50%, 2/4). Additionally, angiomatoid fibrous histiocytoma showed moderate staining (75%, 3/4, 2+). The other tumours with ALK overexpression were pulmonary myoepithelial carcinoma (1/1), EWSR1 -rearranged rhabdomyosarcoma (1/1), desmoplastic small round cell tumour (25%, 1/4), clear cell sarcoma of soft tissue (7.7%, 1/13) and myxoid liposarcoma (6.7%, 1/15). ALK overexpression (IHC≥2+) occurred in both EWSR1 -rearranged and FUS -rearranged tumours. Among fusion partners, FLI1 -rearranged cases had the strongest ALK overexpression (70%, 7/10). Conclusions Our findings demonstrate that ALK overexpression is frequent in FET-rearranged tumours, warranting caution to avoid misdiagnosis, while also presenting potential therapeutic opportunities.